Tangible Experiences of Grace: A Qualitative Investigation of Divine Grace in Roman Catholics - Harwood, Hunter B.; Hall, M. Elizabeth Lewis; Edwards, Keith J.; Hill, Peter C. 1953- (2022)
According to Catholic theology, God offers a gift of love, known as divine grace, to all of humanity. This gift of divine grace is the gift of redemption and forgiveness of sins from God that is offered to everyone who decides to acknowledge and accept it. Grace is central to the lived experience of many Christians. This qualitative study examined how Catholics perceive and experience divine grace using interviews that assessed perceptions of divine grace in 29 practicing adult Catholics. A grounded theory analysis resulted in themes indicating that these Catholics view God’s divine grace as a tangible gift that is undeserved though continuously offered. The participants’ experience of God’s grace is not just an abstract theological concept but an embodied aspect of religious life with which believers can interact in many powerful ways. Three characteristics of God’s divine grace (i.e., salvific grace, cooperation through free will, primacy of conscience and the afterlife) and three mechanisms to experiencing God’s grace (i.e., sacraments, prayer and meditation, saints) are presented.
Keywords: Catholic; Grace; Grounded Theory; Qualitative; Spirituality